THE INTEGRATIVE ORGANIZATIONAL FUNCTION AND APPROACHES IN DEVELOPING THEORY AND PRACTICE TRENDS IN MEDICAL EDUCATION (SCIENCE TIME JOURNAL, 2026)
This article analyzes modern trends in integrating theory and practice in medical education. Contemporary medical training emphasizes that students must not only acquire foundational theoretical knowledge but also develop practical clinical skills effectively. The focus is placed on the integrative organizational function of education, competency-based approaches, innovative pedagogical technologies, and simulation-based exercises to harmonize theoretical knowledge and practical competencies. Furthermore, the article discusses the potential to enhance educational effectiveness through vertical and horizontal integration, case-based learning, and modern assessment methods. The findings highlight that the integration of theory and practice in medical education plays a crucial role in developing clinical reasoning, decision-making skills in complex situations, and professional responsibility among students.